2023
DOI: 10.1186/s12884-023-05387-x
|View full text |Cite
|
Sign up to set email alerts
|

No advantage of single day 6 good-quality blastocyst transfer versus single day 5 poor-quality blastocyst transfer in frozen-thawed cycles stratified by age: a retrospective study

Abstract: Background Blastocyst developmental speed, morphological grading and patient age are associated with pregnancy outcomes of frozen-thawed cycles. This study aimed to compare the clinical and neonatal outcomes between poor-quality D5 blastocysts and good-quality D6 blastocysts stratified by patient age. Methods A total of 1,623 cycles were divided into two groups: group A (n = 723) received one D5 poor-quality blastocyst; group B (n = 900) received o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…This is similar to the conclusions of some studies. For example, a study revealed that the gestational age and birthweight of low-quality blastocysts transferred on D5 did not significantly differ from those of high-quality blastocysts transferred on D6 ( 28 ). A large retrospective study, including data on 7,469 females with singleton births, revealed that both groups had similar outcomes after transferring a high- or non-high-quality blastocyst ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the conclusions of some studies. For example, a study revealed that the gestational age and birthweight of low-quality blastocysts transferred on D5 did not significantly differ from those of high-quality blastocysts transferred on D6 ( 28 ). A large retrospective study, including data on 7,469 females with singleton births, revealed that both groups had similar outcomes after transferring a high- or non-high-quality blastocyst ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results are similar to those of several recent studies (19, 27, 28). He et al (28) divided their study patients into two groups based on age (< 35 years and ≥ 35 years). They observed that the neonatal outcomes of the group with transferred D5 non-excellent embryos were similar to those of the group with transferred D6 excellent embryos in both age groups.…”
Section: Discussionmentioning
confidence: 99%